Accounting systems - Bruce, Ken. (South Melbourne : Nelson, 1999)
An overview of accounting systems. Control over debtors. Control over creditors. Control over cash. Control over inventory. Integrated application exercises...
Keywords: Accounting; Data processing; Accounting; Accounting -- Problems, exercises, etc; Accounting -- Data processing